Effects of Dietary Ca and P Concentrations on Growth Performance of 13- to 25-lb Pigs - F. Wu; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 360 nursery pigs (PIC 1050 × 280, initially 13.3 ± 2.39 lb) were used in a 45-d growth study to determine the effects of feeding 2 standardized total tract digestible (STTD) P and 3 Ca concentrations on growth performance. In a completely randomized design, pens of pigs (10 pigs per pen, 6 pens per treatment) were allotted randomly to 1 of 6 dietary treatments. Dietary treatments were arranged in a 2 × 3 factorial, with 2 levels of STTD P (at or above NRC requirement estimates) and 3 levels of Ca (0.65, 0.90, and 1.20%). Diets formulated to meet NRC P requirement estimates contained 0.45 or 0.40% STTD P in phases 1 and 2, respectively, and diets formulated to exceed NRC P requirements contained 0.56 or 0.52% STTD P in phases 1 and 2, respectively. Diets were provided in 3 phases, with pigs fed experimental diets during phase 1 (d 0 to 10) and phase 2 (d 10 to 24), followed by a common phase 3 diet from d 24 to 45. During the treatment period (d 0 to 24), no Ca × P interactions were observed for ADG and ADFI. Increasing Ca concentration decreased (linear, P = 0.006) ADG, but did not affect ADFI. Feeding high concentrations of STTD P tended to increase (P = 0.084) ADG, but did not affect ADFI, compared with pigs fed STTD P levels recommended by NRC. An interactive effect between Ca and STTD P was observed for F/G (P = 0.018). When diets contained NRC levels of STTD P, pigs fed 1.20% Ca had poorer (P<0.05) F/G than those fed 0.65 or 0.90% Ca; however, when high levels of STTD P were fed, the dietary Ca concentrations did not affect F/G. Day 24 BW decreased (linear, P = 0.006) with increasing Ca concentrations, regardless of the STTD P levels in diets. From d 24 to 45, when all pigs received a common phase 3 diet, no interactive or main effects of Ca and STTD P concentrations were observed for ADG, ADFI, or final BW. However, pigs previously fed increasing concentrations of Ca had improved (linear, P = 0.003) F/G regardless of dietary STTD P content. As a result of this compensatory gain, no treatment effects were observed for the overall growth performance. In conclusion, excess dietary Ca impairs ADG and F/G of nursery pigs, especially in low P content diets. The STTD P levels estimated by NRC meet the requirement of 13- to 25-lb pigs when diets contain low Ca concentrations but are deficient when diets contain more than 0.90% Ca.
Keywords: calcium; nursery pigs; phosphorus